Crystal growth, structure and optical properties of solvated crystalline Tris(8-hydroxyquinoline)aluminum(III)(Alq3). (October 2016) - Wang, Yuan Yuan; Ren, Yan; Liu, Jie; Zhang, Cheng Qian; Xia, Sheng Qing; Tao, Xu Tang
Abstract: Tris(8-hydroxyquinoline)aluminum(III) (Alq3 ) is characterized by crystallization in polymorphism both under vapor deposition and solvent evaporation. In this article, crystal growth of Alq3 in several organic solvents is studied. High quality bulk single crystals or crystalline microstructures are obtained, which depends on the varied conditions of crystallization. Two new crystalline solvates of Alq3 (HCON(CH3 )2 ) and Alq3 ((CH2 OH)2 ) growing in N, N -dimethylformamide (DMF) and ethylene glycol (EG) have been obtained. X-ray diffraction analysis shows that their structures belong to new polymorphism bearing identical crystal symmetry, which is different to any solvated crystal phases reported before. The photoluminescent (PL) properties of the crystalline Alq3 (HCON(CH3 )2 ) and Alq3 ((CH2 OH)2 ) are measured. Both crystals exhibit high quantum yield and long PL lifetime. In addition, the optical waveguide properties of Alq3 (HCON(CH3 )2 ) microstructures are investigated. It shows that solvated single-crystals or microstructures can be used as excellent light-emitting and propagation materials in miniaturized optoelectronic devices. Graphical abstract: Highlights: The growth of Alq3 in several organic solvents has been investigated. Two new solvated single crystals of Alq3 (HCON(CH3 )2 ) and Alq3 ((CH2 OH)2 ) have been grown and solved. The two solvated Alq3 crystals possess strong photoluminescence properties. One-dimensional Alq3 (HCON(CH3 )2 ) microstructures have excellent optical wave guide features.